Table_1_Changes in Activity and Community Composition Shape Bacterial Responses to Size-Fractionated Marine DOM.XLSX - Marta M. Varela; Tamara Rodríguez-Ramos; Elisa Guerrero-Feijóo; Mar Nieto-Cid (2020)
To study the response of bacteria to different size-fractions of naturally occurring dissolved organic matter (DOM), a natural prokaryotic community from North Atlantic mesopelagic waters (1000 m depth) was isolated and grown in (i) 0.1-μm filtered seawater (CONTROL), (ii) the low-molecular-weight (<1 kDa) DOM fraction (L-DOM), and (iii) the recombination of high- (>1 kDa) and low-molecular-weight DOM fractions (H + L-DOM), to test the potential effect of ultrafiltration on breaking the DOM size continuum. Prokaryotic abundance and leucine incorporation were consistently higher in the H + L-DOM niche than in the L-DOM and CONTROL treatments, suggesting a different interaction with each DOM fraction and the disruption of the structural DOM continuum by ultrafiltration, respectively. Rhodobacterales (Alphaproteobacteria) and Flavobacteriales (Bacteroidetes) were particularly enriched in L-DOM and closely related to the colored DOM (CDOM) fraction, indicating the tight link between these groups and changes in DOM aromaticity. Conversely, some other taxa that were rare or undetectable in the original bacterial community were enriched in the H + L-DOM treatment (e.g., Alteromonadales belonging to Gammaproteobacteria), highlighting the role of the rare biosphere as a seed bank of diversity against ecosystem disturbance. The relationship between the fluorescence of protein-like CDOM and community composition of populations in the H + L-DOM treatment suggested their preference for labile DOM. Conversely, the communities growing on the L-DOM niche were coupled to humic-like CDOM, which may indicate their ability to degrade more reworked DOM and/or the generation of refractory substrates (as by-products of the respiration processes). Most importantly, L- and/or H + L-DOM treatments stimulated the growth of unique bacterial amplicon sequence variants (ASVs), suggesting the potential of environmental selection (i.e., changes in DOM composition and availability), particularly in the light of climate change scenarios. ...